Long Term and Remote Health Monitoring with Smart Phones - Kirci, Pinar; Kurt, Gokhan (International Journal of Intelligent Systems and Applications in Engineering, 2016)
The basicÂ  aim of our workÂ  is to provideÂ  solutions with monitoring the heart beat ratesÂ  of disabled or old people. And also we expect to help the people who have specific heart diseasesÂ  like potential cardiac arrests and cardiac pacemaker carriers. Besides in case of emergency situations, our system will produce an immediate alarm to provide urgent help for the patients. In the system, emergency situations depend on the heart beat rates. If the heart beat rates of a person decreases at lower rates compared with normal heart beat rates or if the heart beat rates of a person increases at higher rates compared with normal heart beat rates or ifÂ  big heart beat rate changes occur during the predetermined time period then these situations will be evaluated as emergency situations and these situations should be announced to considered people and places like hospitals, patientâs doctor and patientâs family members. The proposedÂ  system colloborates with smartphones and includes sensors to collect data from the patient. Also the system is used to process and compare data with pre defined normal heart beat rates by patientâs doctor and to notice if there is an emergency situation. Besides, in case of an emergengy situation, to inform considered people. But if there is not an emergengyÂ  situation exists, then the system stores the collected data and sends them asÂ  daily and weekly graphics to the patientâs doctor. These graphics are collected as a result of definite dailyÂ  activities like sleeping, sitting, standing, walking and jogging. The results are compared with the patientâs doctorâs stated normal heart rate intervals for every activity period. Furthermore, our proposed system structure includes heart pulse sensor, a smartphone screen, bluetooth interface and memory.